Diagnóstico y planeación financiera a la compañía Enrique Ullauri Materiales de Construcción Cia. Ltda. de la ciudad de Catamayo. Periodo 2022-2026 - Salazar Carrillo, Edison Alexander (2023)
The research work entitled "DIAGNOSTIC AND FINANCIAL PLANNING FOR THE COMPANY ENRIQUE ULLAURI MATERIALES DE CONSTRUCCIÓN CIA. LTDA. OF CATAMAYO CITY, PERIOD 2022-2026", it was developed according to the established in the Regulations of Academic Regime of the Universidad Nacional de Loja previous to get the degree and diploma of Engineer in Accounting and Audit Public Accountant-Auditor, and which will serve as a contribution so that the general manager and the partners can take the required corrective procedures, and improve the economic-financial situation, thus maximize the economic benefits. During the first specific objective, it was gathered the financial statements and through an unstructured interview to the chief financial officer, it was carried out a financial diagnostic to determine the financial and economic structure and the variations that were presented in the analyzed periods, it was applied the financial ratios as well as it was elaborated a SWOT matrix, which showed that the current assets present a high level of investment of $426,924.36 in the year 2020 and $675. 652.16 in the year 2021, and that the liability has a higher level than the patrimony, it indicates that the company is in the hands of third parties; while the economic structure reflects a high level of income of $1,018,424.06 in the year 2020 and $1,433,142.90 in the year 2021, based on the results obtained, it was carried out the financial planning. In order to achieve the second specific objective, it was developed the sales and purchases forecasts using the seasonal index method on the basis of the sales and purchases history gathered on a monthly basis for the year 2021, thus it provided a proportional increase in sales and purchases for the five projected years; then it was determined the cash inflows and outflows in order to develop the cash budget, which shows as a result cash surpluses for the year 2022 is $160. 142.60, in the year 2023 it has a value of $238,780.73, the year 2024 is $338,986.13, the year 2025 corresponds to $463,609.58 and for the year 2026 it is $615,816.64. As a third specific objective, it was prepared the proforma financial statements for the period 2022-2026 thus, establish expected estimates of assets, liability, patrimony, income, costs, expenses, and profit in order to provide a view of the future economic-financial situation of the company; as a result, the profits presented in the Proforma Income Statement reflect that for the year 2022 the estimated profit is $19,791.67. 791.67; in the year 2023 it will get $38,917.98; for the year 2024 it will be $51,687.47; in the year 2025 it will get $66,062.44 and finally in the year 2026 it will be $82,181.38; despite making profits, these are still unimportant in relation to the projected revenues. Finally, a break-even point was developed for the five projection periods to determine the minimum sales volume for the company to cover costs and expenses.